Bahasa Arab di Pesantren Modern - Sahana Anggian, Lutvi Ali (Institut Agama Islam Riyadlotul Mujahidin Ngabar (IAIRM) Ponorogo, 2023)
Islamic boarding schools are the oldest places of learning in Indonesia. Their existence in learning Arabic can be seen from the success of Islamic boarding schools in producing young people who are able to speak Arabic and master the four Arabic skills proportionally. In practice, Islamic boarding schools use a learning model that is considered effective for training and improving students' Arabic language skills. Santri learn Arabic in which Latin writing is not found in the book, there is only Arabic writing without a vowel. Santri are required to be able to read, understand, what has been conveyed by an ustadz, besides that in daily conversations students are required to use language (Arabic and English) because in modern Islamic boarding schools there is a language environment. Arabic is a language that is recognized internationally as a means of world communication. The spread of Arabic throughout the world until now has its own significance for the development of linguistics. Arabic entered Indonesia through trade routes at the same time as the arrival of Islam. The quantity of Muslims spread throughout the world also influences the pattern of the spread of Arabic when viewed from a grammatical perspective (I'rob), Arabic has two unique grammatical sides which students must master both.